2020
DOI: 10.1007/s00167-019-05824-5
|View full text |Cite
|
Sign up to set email alerts
|

Patients undergoing shoulder surgery have high preoperative expectations

Abstract: Purpose The primary aims of this study were to (1) assess the preoperative expectations of patients undergoing shoulder surgery, and (2) determine the relationship between preoperative patient demographics, PROs, and preoperative patient expectations. It was hypothesized that younger patients with worse function and worse health status had higher expectations of shoulder surgery. Methods Data from a total of 319 patients (319 shoulders) from 2015–2018 were analyzed. Patients completed a series of questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…The relationship between opioids and psychosocial aspects of health is also complex. Evidence has suggested that opioid use may result in unrealistic expectations about pain management after surgery 37 and may aggravate the anxiety associated with painful stimuli. 53 Perhaps, then, it is not surprising that a relationship with opioid misuse exists between both active cigarette smoking and drug/alcohol abuse syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between opioids and psychosocial aspects of health is also complex. Evidence has suggested that opioid use may result in unrealistic expectations about pain management after surgery 37 and may aggravate the anxiety associated with painful stimuli. 53 Perhaps, then, it is not surprising that a relationship with opioid misuse exists between both active cigarette smoking and drug/alcohol abuse syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings agree with those identified in total hip and knee arthroplasty studies, which have demonstrated increased rates of infections, 10 revision surgery, 6,7,56 and readmissions 56 in patients taking opioids before surgery. There are several mechanisms by which preoperative opioid use may be driving these complications, including increased postoperative analgesic requirements, 1,35,57,58 unrealistic postoperative expectations for surgery, 34 increased dissatisfaction with surgery, 22,30 and opioid-associated delayed wound healing and impaired immunological functioning. 39,49 Furthermore, we add to the literature another risk factor for detrimental postoperative outcomes in those undergoing RCR, which previously included patient age, 29 body mass index, 5 comorbidities, 46,53 open repair, 38 and preoperative and intraoperative steroid injections.…”
Section: Discussionmentioning
confidence: 99%
“…We chose to include adolescents to better elucidate any possible relationships between age and expectations and the youngest patient in the cohort was 15 years old. 35,36 All enrolled patients were given the following questionnaires preoperatively: Patient-Reported Outcome Measurement Information System (PROMIS) PF, PROMIS pain interference, PROMIS fatigue, PROMIS social satisfaction, PROMIS anxiety, PROMIS depression, Brief Michigan Hand Questionnaire, MODEMS expectations questionnaire, Tegner activity scale (Tegner), Marx activity rating scale, and numeric pain scale (NPS) for both the operative hand and the rest of the body. MODEMS asks patients what results they expect from their treatment on a five-point Likert scale ranging from "not at all likely" (1) to "extremely likely" (5).…”
Section: Methodsmentioning
confidence: 99%